Successful Stent Graft Insertion for Endovascular Aneurysm Repair and Closure of Patent Ductus Arteriosus in an Adult Patient - Toshiki Kuno; Koji Tsutsumi; Yohei Numasawa (Case Reports in Cardiology)
Patent ductus arteriosus (PDA) is sometimes undetected until adulthood, and surgical closure of a PDA is dangerous because of the calcification of the ductus. Percutaneous approaches such as coil embolization and use of a PDA occluder are less invasive; however, these devices are not suitable for PDA with thoracic aortic aneurysm (TAA). We present the case of a 72-year-old female patient who underwent successful stent graft insertions for PDA with TAA.